A Disaster Response and Management Competency Mapping of Community Nurses in China. - Yu Luo; Ling Liu; Wen-Quan Huang; Ya-Na Yang; Jie Deng; Chun-Hong Yin; Hui Ren; Xian-Yuan Wang (Tehran University of Medical Sciences, 2013)
It is widely accepted in many parts of the world thatcommunity nurses are of vital importance in various phases of disaster response and management. In China, however, it is not clear whether the Chinese community nurses are able to assume disaster-related duties due to the lack of a systematic assessment.A pre-designed and well-tested questionnaire was employed to evaluate the competency in disaster response and management among 205 valid registered Chinese community nurses between September and October 2009. Statistical analyses were performed with SPSS Version 13.0 using one way ANOVA, Least Significant Difference (LSD) and multiple stepwise regression analysis.This group of Chinese community nurses scored at an intermediate level of competency (a score of 3.68 (SD 0.48) out of a perfect score of 5) in disaster response and management, suggesting that they have the basic ability to participate in disaster-related nursing. Four factors, namely, Experiences in Disaster Relief, Participation in Disaster Training, the Age and Duration in Job, were identified to be the predominant factors contributing significantly to the integrated competency in disaster response and management of an individual.Most of the Chinese community nurses have basic qualifications and competencies to undertake the responsibilities of disaster response and management. However, more targeted disaster training including virtual-reality based drills should be provided in order to improve their competency.